What really matters when choosing a hotel? The case of middle east tourists in Kuala Lumpur, Malaysia / Fazuin Mohd. Yusoff and Flora Shumin Chang Abdullah - Mohd. Yusoff, Fazuin; Chang Abdullah, Flora Shumin (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2010)
The purpose of this study is to identify Middle East tourists' hotel selection attributes in Kuala Lumpur. Hotel selection dimensions identified from previous researches were used to help develop the framework of this descriptive study. Four important hotel attribute variables identified were location, services, cleanliness and facilities. Pilot test was conducted before the questionnaires were distributed to the Middle East tourists staying at the five star hotels within the Kuala Lumpur Golden Triangle area. Data obtained was analyzed using Statistical Packages of Social Science (SPSS) and descriptive analysis was used to determine the most significant Middle East tourists' hotel selection attributes in Kuala Lumpur. Findings of the study will help hotel operators to understand and serve Middle East tourists better.